Assessment of the use of FEM for computation of Electromagnetic Forces, Losses and Design of Transformers. (April 2020) - Vibhuti,; Walia, Genius; Bhalla, Deepika
Abstract: This paper reviews the published work on power transformers for assessment of the electrical, magnetic losses, and electromagnetic forces produced during normal and short circuit conditions. The different methods used are analytical method, integral equation method, boundary element method, and finite element method (FEM). The copper losses and eddy currents within the copper conductors/windings need to be assessed to estimate the heat generate and compute the efficiency. The knowledge of the eddy current losses in the core and stray losses in each component of the transformer can help in the design improvement. Earlier 2D FEM and now 3D FEM has been used to evaluate the electromagnetic flux under normal conditions, the effect of the in-rush phenomenon, assessment of mechanical strength of windings, insulation, computation of short circuit forces and need of the mechanical support components during fault conditions. This paper gives an overview of the work done on the computation of electromagnetic forces, losses, and design of transformers using FEM to assess the scope for further work.